The Role of the Climate Technology Centre and Network as a Climate Technology and Innovation Matchmaker for Developing Countries - Lee, Woo Jin; Mwebaza, Rose (My University, 2020)
In this paper, the role of a matchmaker in transferring climate technologies to developing countries was explored from the perspective of open innovation. As the United Nations Framework Convention on Climate Change’s Technology Mechanism, the Climate Technology Centre and Network (CTCN) has strong convening power amongst the stakeholders who are responsible for climate actions in their country. Our research identified that the CTCN has successfully provided “4 openness” models (open network, open request for Technical Assistance, open technology transfer and finance, and open knowledge for the public) to global partners through its technical assistance (TA) services. Then, on the basis of previous empirical Technical Assistance data and network management a new open innovation model was proposed by considering the CTCN matchmaking activities with key stakeholders (innovation networks) during the climate technology transfer processes. This model explains that the role of the CTCN and innovation networks such as academia/research institutions, governments, and the private sector can be interpreted as outside-in innovation at the first technology outsourcing stage, coupled innovation at the second technology research, development, and demonstration (RD&D) stage, and inside-out innovation at the third technology diffusion stage. Moreover, further matchmaker’s approaches for supporting developing countries to establish a conducive and sustainable innovation system were suggested for the extension of our new model.
Keywords: climate technology; open innovation; technical assistance; matchmaker; innovation system